Discovering cancer immunotherapy targets in vivo - Zhou, Penghui (Landes Bioscience, 2014)
A key challenge facing the cancer immunology field is the discovery of the most suitable targets for therapeutic intervention. We recently reported a novel RNA-interference (RNAi)-based approach for systematic discovery of such targets in the tumor microenvironment in vivo utilizing pooled shRNA libraries as a screening tool. Here, we discuss applying this unbiased method to develop innovative cancer therapeutics.